Anti- Bullying Educational Strategy in an Effort Strengthen children’s Mental Health in MIN 1 Malang - Sakarina, Ainayya Nabila; Ishomuddin, Ishomuddin; Mukhlis, Fahrudin (ISTAWA, 2024)
Bullying is becoming more and more prevalent and is very concerning. Both victims and perpetrators can experience serious mental health issues. To overcome this, it is important to strengthen the mentality. As Ibn Sina said, the human soul is the controller of the body and mind. If a child's mentality is disturbed, his learning ability and attitude will also be affected. MIN 1 Malang City has taken a good step by running the Anti Bullying program with the strategies that have been implemented. With this article. The research aims first, to find out the anti-bullying education strategy in an effort to strengthen children's mentality at MIN 1 Malang City. Second, to determine the success of the anti-bullying program at MIN 1 Malang City. The research method uses a descriptive qualitative approach with a case study research type. Theresults of the study are by having a significant strategy in efforts to strengthen children's mentality, namely with spiritual education through Islamic values. Socialization that teaches bullying recognition, empathy, and emotional support, social skills. Scouting activities teach independence and self-confidence. Reward teaches the consequences that will occur if individuals do bad things. Advice warns students and establishes closeness between teachers and students. The success of anti-bullying education cannot be separated from the support of all and a holistic approach. Bullying semakin sering terjadi dan sangat mengkhawatirkan. Baik korban maupun pelaku, keduanya bisa mengalami masalah Kesehatan mental yang serius. Untuk mengatasi hal ini, penting untuk memperkuat mental. Seperti yang dikatakan Ibnu Sina, jiwa manusia adalah pengendali tubuh dan pikiran. Jika mental anak terganggu, kemampuan belajar dan sikapnya juga akan ikut terpengaruhi. MIN 1 Kota Malang telah mengambil Langkah baik dengan menjalankan program Anti Bullying dengan strategi yang telah dilaksanakan. Dengan adanya artikel ini. Penelitian bertujuan pertama, untuk mengetahui strategi Pendidikan anti bullying dalam upaya penguatan mental anak di MIN 1 Kota Malang. Kedua, untuk mengetahui keberhasilan program anti bullying di MIN 1 Kota Malang. Metode penelitian menggunakan pendekatan kualitatif deskriptif dengan jenis penelitian studi kasus. Hasil penelitian yaitu dengan memiliki strategi yang signifikan dalam upaya penguatan mental anak yaitu dengan Pendidikan spiritual melalui nilai-nilai islam. Sosialisasi yang mengajarkan pengenalan bullying, empati, dan dukungan emosional, keterampilan sosial. Kegiatan pramuka mengajarkan kemandirian dan kepercayaan diri. Reward (diberi pahala) mengajarkan konsekuensi yang akan terjadi jika individu melakukan hal yang tidak baik. Nasihat menginatkan siswa dan menjalin kedekatan antara guru dan siswa. Keberhasilan Pendidikan anti bullying tidak luput dari dukungan semua dan pendekatan holistik.Keywords: Bullying, Anti-bullying Education, Mental Strengthening, Al-Qur’an